Perbandingan Algoritma Genetika dan TSP Untuk Optimalisasi Jaringan Akses Fiber To The Home - Try Feby Ramadonna; Ade Silvia; Ciksadan Ciksadan (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Genetic algorithm and TSP are  methods that can be solve optimization problem  of route or path. This paper discusses the application of genetic algorithms and Traveling Salesman Problem modeling (TSP) to those problems. The process of genetic algorithm is the principle of natural selection to find the shortest route, while TSP is Optimization issues to find the shortest journey for traveling traders who want to visit several cities. In addition, this paper compares genetic algorithms with TSP in finding the shortest route. The shortest route search is performed on the ODP device (Optical distribution point) on the FTTH access network passed by the salesman. The results is an optimal routes using genetic algorithms at 4.46 km, on 38 generations of 50 generations. While in TSP modelling is obtained an optimal route at 4.45 km on the second experiment of the twelve experiments. This route will affect the performance of the data transmission process on the FTTH access network, when this network attenuation is less than 28 dB (based on International Telecommunication Union standard). Keywords—  TSP, Genetic Algorithm, Optimization, FTTH.